2021
DOI: 10.3389/fimmu.2021.763831
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HDAC6 in Autophagy and NLRP3 Inflammasome

Abstract: Autophagy fights against harmful stimuli and degrades cytosolic macromolecules, organelles, and intracellular pathogens. Autophagy dysfunction is associated with many diseases, including infectious and inflammatory diseases. Recent studies have identified the critical role of the NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasomes activation in the innate immune system, which mediates the secretion of proinflammatory cytokines IL-1β/IL-18 and cleaves Gasdermin D to induce pyroptosis in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 171 publications
(299 reference statements)
2
36
0
Order By: Relevance
“…The possibility that HDACs are involved in the osteoclast formation in the pathogenesis of gout has been proposed. HDAC6 inhibition suppressed NLRP3 inflammasome activation by attenuating the transcription of NF-κB in the priming process and by reducing the expression of mature caspase-1, ultimately resulting in reduced production of IL-1β [ 17 ]. Cleophas et al showed that the HDAC1/2 inhibitor Romidepsin potently decreased the production of numerous inflammatory cytokines including IL-1β, IL1Ra, IL-6, and IL-8 in PBMCs incubated with MSU and palmitic acid, suggesting HDAC1/2 inhibition as a novel therapeutic strategy in acute gout [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that HDACs are involved in the osteoclast formation in the pathogenesis of gout has been proposed. HDAC6 inhibition suppressed NLRP3 inflammasome activation by attenuating the transcription of NF-κB in the priming process and by reducing the expression of mature caspase-1, ultimately resulting in reduced production of IL-1β [ 17 ]. Cleophas et al showed that the HDAC1/2 inhibitor Romidepsin potently decreased the production of numerous inflammatory cytokines including IL-1β, IL1Ra, IL-6, and IL-8 in PBMCs incubated with MSU and palmitic acid, suggesting HDAC1/2 inhibition as a novel therapeutic strategy in acute gout [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HDAC6 is involved in the activation of the NACHT, LRR, and PYD-domains-containing the protein 3 (NLRP3) inflammasome, playing an important role in the pathological mechanism of gout [ 17 ]. In addition, HDAC1/2 dual inhibition was shown to be an effective strategy in treating gout [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mechanisms have been proposed to explain the interactions between the NLRP3 inflammasome and autophagy, including autophagy activation by inflammatory signaling via limited IL-1b production and targeting ubiquitinated inflammasomes (13). In neurological diseases, non-coding RNA, bio-enzymes, and small molecular compounds have been implicated in the interplay between ubiquitination and autophagy of NLRP3 (46)(47)(48). In LPSstimulated microglia, CB2R activation decreased NLRP3 expression associated with formation of autophagosomes, resulting in accumulation of LC3B and exhaustion of p62.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of high OFD1 levels in patient organoids compared to the control, despite an elevated autophagic flux, suggests alternative mechanisms. HDAC6 has also been demonstrated to promote autophagosome maturation ( 108, 109 ) as well as deacetylate microtubules to impede intracellular trafficking, which is a key driver of primary cilium disassembly. Higher expression of HDAC6 in patient organoids could explain both the failure of docking of pre-ciliary vesicles ( 33 ) and elevated autophagic flux in patient photoreceptors.…”
Section: Discussionmentioning
confidence: 99%